The Impact of Government Policy Marketing Mix on The Income of Silk Entrepreneurs - Abbas, Muchlis (Jurnal Manajemen Bisnis, 2023)
The approach used in this research is correlative research which explains the influence of the marketing mix, culture and government policy on income, which in its implementation uses data collection techniques such as documentation, observation, questionnaires and interviews. The population in this study were all natural silk entrepreneurs totaling 200 people from three regions, namely: Soppeng, Wajo and Enrekang. The results of this research show that (1) the marketing mix has a positive and significant effect on the income of silk entrepreneurs (2) Supply Chain has a positive and significant effect on the income of silk entrepreneurs (3) Government policy has a positive and significant effect on the income of silk entrepreneurs (4) The income of silk entrepreneurs positive and significant effect on marketing performance (5) Marketing Mix has a positive and significant impact and no significant effect on marketing performance (6) Supply Chain has a positive and significant effect on marketing performance (7) Government policy has a positive and significant effect on marketing performance (8 ) Marketing mix has a positive and significant effect on marketing performance through the income of silk entrepreneurs (9) Supply Chain has a positive and significant effect on marketing performance through the income of silk entrepreneurs (10) Government policy has a positive and significant influence on marketing performance through the income of silk entrepreneurs